The Implementation of Knowledge Assessment In Curriculum 2013 in Elementary Schools - Ulumudin, Ikhya; Aisha, Asma; Widiputera, Ferdi (Technium Social Sciences Journal, 2020)
The purpose of this study was to determine the understanding and implementation of the knowledge assessment carried out by teachers at the elementary school level starting from planning, implementing, processing results, utilizing results and identifying problems in implementing knowledge assessment. This study used a qualitative approach. Research took place in Sleman Regency, Yogyakarta Province. The research subjects were public and private elementary school teachers who had taught in classes applying Curriculum 2013. The research instruments consisted of questionnaires and FGD (focus group discussion) guidelines. The results showed that on the assessment planning, teachers lack understanding in the formulation of instrument outlines, especially in describing the Basic Competency into the question indicators, making questions about the aspects of knowledge based on the indicator, and making scoring guidelines. In the implementation of the assessment, some teachers did not understand the use of various assessment techniques for knowledge aspect. The frequency of carrying out daily knowledge assessments varies, including for every KD (basic competency), every day, for every sub-theme, for several sub-themes, and for every theme. In assessment result processing, some elementary school teachers still lack understanding about processing and reporting in knowledge assessment whether in the form of numeric scores, predicates, and descriptions. In the utilization of the assessment, all elementary school teachers in Sleman Regency have applied the assessment of learning function as each daily assessment result is used by the teacher to review student achievement in each KD. In the aspect of assessment for learning, some teachers have made use of assessments for remedial activities and lesson enrichment and to evaluate the learning process. Lastly, regarding the use of assessment as learning, some teachers have provided results of student assessment and used it to provide guidance and advice to students.